Total Phenolic, Flavonoid Contents, and Antioxidant Activities of Fruit, Seed, and Bark Extracts of Zanthoxylum armatum DC. (16th March 2020) - Phuyal, Nirmala; Jha, Pramod Kumar; Raturi, Pankaj Prasad; Rajbhandary, Sangeeta
Abstract : Natural antioxidants present in several medicinal plants are responsible for inhibiting the harmful effects of oxidative stress. These plants contain polyphenols and flavonoids that act as free radical scavengers and reduce oxidative stress and may be an alternative remedy to cure various harmful human diseases. This study aims to quantify the total phenolic and flavonoid contents (TPC and TFC) and antioxidant properties of methanol extracts of fruits, seeds, and bark of an important medicinal and aromatic plant, Zanthoxylum armatum collected from wild and cultivated populations in Nepal. TPC was determined by Folin–Ciocalteu colorimetric method using gallic acid as standard, and various concentrations of the extract solutions were measured at 760 nm. TFC was calculated by aluminum chloride colorimetric assay. Quercetin was used as standard, and the absorbance was measured at 510 nm. The antioxidant potential of the different extracts was estimated by DPPH free radical scavenging assay, and the absorbance was measured at 517 nm. The highest TPC value was 226.3 ± 1.14 mg GAE/g in wild fruits, and the lowest was 137.72 ± 4.21 mg GAE/g in cultivated seeds. Similarly, the highest TFC value was 135.17 ± 2.02 mg QE/g in cultivated fruits, and the lowest was 76.58 ± 4.18 mg QE/g in cultivated seeds. The extracts showed variable antioxidant properties. The fruits exhibited excellent antioxidant properties with IC50 values of 40.62  μ g/mL and 45.62  μ g/mL for cultivated and wild fruits, respectively. Similarly, the IC50 values of the bark were 63.39  μ g/mL and 67.82  μ g/mL, respectively, for cultivated and wild samples. And the least antioxidant capacity was shown by the seeds extract with IC50 values of 86.75  μ g/mL and 94.49  μ g/mL for wild and cultivated seeds, respectively. The IC50 value of the standard ascorbic acid was 36.22  μ g/mL. Different extracts of Z . armatum contain considerable amount of phenols and flavonoids, including antioxidant properties, suggesting the potential use of this species in pharmacy and phytotherapy as a source of natural antioxidants.